2022
DOI: 10.3390/socsci11050210
|View full text |Cite
|
Sign up to set email alerts
|

Muted Voices: The Underrepresentation of Women in COVID-19 News in Portugal

Abstract: During the COVID-19 pandemic, the Portuguese media seemed to contribute to the symbolic annihilation of women. In spite of the fact that women play leading political roles as the Minister of Health and the Directorate-General of Health, women were almost mute in the COVID-19 news that was published in the Portuguese daily national press. In a sample of more than 6000 news sources, women account for less than 20% of them. Their lack of visibility in the news deepens the existing asymmetries of gender and amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Against this background, #systemrelevant connected multiple overlapping discourses around health care, working conditions, and gendered inequality: From private, unpaid care work and homeschooling to increased domestic violence against women during the lockdown-women's specific burdens became more visible. But women's representation and voice in coverage of the pandemic remained at low levels in Germany, like in many other countries (e.g., Araújo et al, 2022;Jones, 2020). It was mainly male experts who explained the burdens on women during the pandemic (Prommer et al, 2021).…”
Section: #Systemrelevant As a Case Studymentioning
confidence: 99%
“…Against this background, #systemrelevant connected multiple overlapping discourses around health care, working conditions, and gendered inequality: From private, unpaid care work and homeschooling to increased domestic violence against women during the lockdown-women's specific burdens became more visible. But women's representation and voice in coverage of the pandemic remained at low levels in Germany, like in many other countries (e.g., Araújo et al, 2022;Jones, 2020). It was mainly male experts who explained the burdens on women during the pandemic (Prommer et al, 2021).…”
Section: #Systemrelevant As a Case Studymentioning
confidence: 99%
“…Different than expected, this has not changed during the pandemic (Prommer & Stüwe, 2020). General findings on sourcing women as experts in pandemicrelated issues show continued underrepresentation in legacy (news) media (Araújo et al, 2022;Jones, 2020;Kassova et al, 2020). Macharia (2020, p. 35) reveals that less than a third of those represented as experts or commentators in Covid-19 news are female (29%), and almost half of the ones speaking out of personal experience are women (45%).…”
Section: Care Work Female Invisibility and Gendered Structures Of (So...mentioning
confidence: 99%
“…Within science-related news coverage, there is often a dearth of female experts quoted as compared to their male counterparts (e.g. Araújo et al, 2022; Fletcher et al, 2021; Kitzinger et al, 2008; Niemi and Pitkänen, 2017). For example, Kitzinger et al (2008) examined gender representations within science-related news stories published in Britain over a 6-month period and concluded that males were cited at a much higher frequency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When it comes to news media coverage of COVID-19 in general, furthermore, female researchers and healthcare workers are underrepresented in the news media (e.g. Araújo et al, 2022; Fletcher et al, 2021). Now, news media organizations, such as The New York Times , have recognized the gender gap within their quoted sources (Taub and Fisher, 2018) which has led to a mindful effort to include more female voices in their reporting.…”
mentioning
confidence: 99%